Universal professional skills of the modern teacher within the framework of digitalization of higher education - Liliia R. Nurtdinova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The European paradigm is one of the main guiding vectors for Russian education. The introduction of the main aspects of the Bologna process dictates the continuous development of not only the educational process, but also all the people involved in it, including teachers. The necessity to keep up with the changes and meet the latest educational requirements and standards modifies the competencies of the teacher and forms new edges of understanding his profession. In this regard, this paper discusses the key competencies of a teacher necessary for a modern and future specialist. At the beginning of the research, a review of scientific works on this topic is carried out, then a comparative analysis of educational international conferences is used, followed by SEO analysis, on the basis of which key prospects and guidelines for the development of education for the coming years are highlighted. Based on the results of the study, the author proposes a list of universal competencies for the teacher that meet the standards and identified educational goals.